Hierarchical self-assembled Bi2S3 hollow nanotubes coated with sulfur-doped amorphous carbon as advanced anode materials for lithium ion batteries - Dong, Yucheng (2020)
Bismuth sulfide (Bi2S3) is considered as a promising anode material for lithium ion batteries (LIBs) owing to its high theoretical specific capacity and intriguing reaction mechanism. However, capacity fading and cycling instability due to volume variation during the lithiation/delithiation process still remain a great challenge. Herein, we proposed a simple glucose assisted hydrothermal strategy and followed a post-treatment process to prepare hierarchical sulfur-doped carbon Bi2S3 (Bi2S3@SC) hollow nanotubes that self-assembled into sulfur-doped amorphous carbon coated Bi2S3 nanocrystals as building blocks. Glucose plays a decisive role in the formation process of Bi2S3 nanocrystals and subsequent self-assembly, forming Bi2S3@SC hollow nanotubes. The polysaccharide shell formed on the surface of Bi2S3 nanocrystals during the hydrothermal process was transformed into the sulphur-doped amorphous carbon layer after the post-treatment process. Electrochemical tests reveal that the resulting composites exhibit excellent electrochemical performance with a highly reversible cycling capacity of ∼950 mA h g−1 at a current density of 100 mA g−1, as well as a good rate capability and significantly enhanced cycling stability derived from their unique structural features, thus demonstrating the potential of Bi2S3@SC hollow nanotubes as high performance anode materials for LIBs. The analysis of electrochemical kinetics confirmed that the pseudocapacitive behavior dominates the overall storage process of Bi2S3@SC hollow nanotubes.